MARCAN USAGE: NOTES, CRITICAL AND EXEGETICAL, ON THE SECOND GOSPEL - Turner, C. H. (The journal of theological studies, 1924)
C. H. TURNER; MARCAN USAGE: NOTES, CRITICAL AND EXEGETICAL, ON THE SECOND GOSPEL, The Journal of Theological Studies, Volume os-XXV, Issue 100, 1 July 1924, Pag